Perilaku Kepemimpinan Kepala Sekolah dalam Peningkatan Kinerja Guru pada SD Negeri 2 Lamcot Kabupaten Aceh Besar - Suraiya, Suraiya; Kasmini, Lili; Syarfuni, Syarfuni (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The aim of this research is to determine the leadership behavior of school principals in improving teacher performance at State Elementary School 2 Lamcot, Aceh Besar Regency. Research using a qualitative approach with data collection techniques, documentation, observation, and interviews. This research shows that the preparation of school principal policies in improving teacher abilities is by making written and verbal rules in accordance with the school's vision and mission by involving teachers, school supervisors and school committees regarding activities to increase teacher abilities. The results of this policy become guidelines for teachers to carry out their duties better to achieve an increase in the quality of education; school principal program as a leader in improving teacher discipline by using effective communication (not rude, carrying out direct supervision, not arrogant and authoritarian), preparing Teacher Working Group programs, seminars, and workshops. With this program showing encouraging results, teachers are more disciplined so they can complete it well; the principal's strategy as a leader in increasing teacher responsibility by involving all teachers and providing direct examples; Factors that influence the leadership of school principals in improving teacher performance are the principal's desire to improve school performance so that it has better achievements at the Acehnese and national levels